From the Battle of Curuzu to the fall of Humaita (1866-1868): tactical issues - Clemente Goncalves, Leandro Jose [UNESP] (Ministerio Marinha, Serv Documentacao Geral Marinha, 2018)
The present article seeks to explain the importance of the siege and fall of Humaita's fortress to the achievement of the strategic objectives of the Triple Alliance in its fight against the government of Solano Lopez. His focus, however, is on understanding the tactical aspects that permeated the siege campaign against that fortress.
Keywords: Humaita; Paraguay; war